Contribution of Various Types of Transfusion to Acute and Delayed Intracerebral Hemorrhage Injury - Kumar, Siddharth; Andoniadis, Matthew; Solhpour, Ali; Asghar, Salman; Fangman, Madison; Ashouri, Rani; Doré, Sylvain (Frontiers in Neurology, 2021)
Intracerebral hemorrhage (ICH) is the second most prevalent type of stroke, after ischemic stroke, and has exceptionally high morbidity and mortality rates. After spontaneous ICH, one primary goal is to restrict hematoma expansion, and the second is to limit brain edema and secondary injury. Various types of transfusion therapies have been studied as treatment options to alleviate the adverse effects of ICH etiopathology. The objective of this work is to review transfusions with platelets, fresh frozen plasma (FFP), prothrombin complex concentrate (PCC), and red blood cells (RBCs) in patients with ICH. Furthermore, tranexamic acid infusion studies have been included due to its connection to ICH and hematoma expansion. As stated, the first line of therapy is limiting bleeding in the brain and hematoma expansion. Platelet transfusion is used to promote recovery and mitigate brain damage, notably in patients with severe thrombocytopenia. Additionally, tranexamic acid infusion, FFP, and PCC transfusion have been shown to affect hematoma expansion rate and volume. Although there is limited available research, RBC transfusions have been shown to cause higher tissue oxygenation and lower mortality, notably after brain edema, increases in intracranial pressure, and hypoxia. However, these types of transfusion have varied results depending on the patient, hemostasis status/blood thinner, hemolysis, anemia, and complications, among other variables. Inconsistencies in published results on various transfusion therapies led us to review the data and discuss issues that need to be considered when establishing future guidelines for patients with ICH.